American relics and the politics of public memory - Dennis, Matthew, 1955- (Public history in historical perspective., 2023)
"The gold epaulettes that George Washington wore into battle. A Union soldier's bloody shirt in the wake of the Civil War. A crushed wristwatch after the 9/11 attacks. The bullet-riddled door of the Pulse nightclub. Volatile and shape-shifting, relics have long played a role in memorializing the American past, acting as physical reminders of hard-won battles, mass tragedies, and political triumphs. Surveying the expanse of U.S. history, "American Relics and the Politics of Public Memory" shows how these objects have articulated glory, courage, and national greatness as well as horror, defeat, and oppression. While relics mostly signified heroism in the nation's early years, increasingly, they have acquired a new purpose--commemorating victimhood. The atrocious relics of lynching and the looted remains of Native American graves were later transformed into shameful things, exposing ongoing racial violence and advancing calls for equality and civil rights. Matthew Dennis pursues this history of fraught public objects and assesses the emergence of new venues of memorialization, such as virtual and digital spaces. Through it all, relics continue to fundamentally ground and shape U.S. public memory in its uncertain present and future"--